2006
DOI: 10.1227/01.neu.0000235197.36789.42
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Nerve Guide Implants in Humans: A Comprehensive Survey

Abstract: To treat longer defects, further implant development is needed, a goal that could be achieved, for example, by more closely imitating the intact nerve architecture and regulatory cell-cell interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
149
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(157 citation statements)
references
References 40 publications
0
149
0
8
Order By: Relevance
“…PGA is degraded into lactic acid in 6-12 months [73,90]. Therefore, critics claim that PGA may degrade faster than the regeneration process and resulting lactic acid may a have toxic effects [84,[141][142][143]. Dellon and Mackinnon [144] were the first to report the use of PGA conduits as secondary reconstitution of digital nerve defects 3 cm or smaller in 15 clinical cases in monkeys.…”
Section: Polyglycolic Acidmentioning
confidence: 99%
“…PGA is degraded into lactic acid in 6-12 months [73,90]. Therefore, critics claim that PGA may degrade faster than the regeneration process and resulting lactic acid may a have toxic effects [84,[141][142][143]. Dellon and Mackinnon [144] were the first to report the use of PGA conduits as secondary reconstitution of digital nerve defects 3 cm or smaller in 15 clinical cases in monkeys.…”
Section: Polyglycolic Acidmentioning
confidence: 99%
“…Though an autologous nerve graft is the gold standard of nerve graft repair, it has several disadvantages, including the need for an extra incision, loss of donor nerve function, mismatch in size between the donor nerve and the injured nerve, and a limited availability of donor nerve. A diverse array of synthetic and natural materials has been studied in peripheral nerve repair, but these studies have shown limited success [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…30 mm nin altındaki kısa periferal sinir defektlerinde endike olduğu bildirilmiştir. 34 Otojen kaynaklı entübülasyon gereçleri; ven, kollajen, kas ve fasyalardır. Alloplastik kaynaklı entübülasyon gereçle-rinden popüler olanları ise; politetrafloroetilen (goretex), silikon ve polyglikolik asit (neurotube) sayılabilir.…”
Section: Entübülasyonunclassified